2019
DOI: 10.1016/j.jvscit.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Reverse slider technique using the Endurant stent graft for accurate proximal sealing in hostile neck endovascular aneurysm repair

Abstract: This report introduces the reverse slider technique to obtain proximal sealing effectively in endovascular aneurysm repair in short or angulated necks. It is the deployment process of the stent graft main body by repeatedly rotating and reversing the external slider with slight loosening of the suprarenal stent. This method helps obtain accurate placement of the proximal edge and effective sealing on the greater curvature side even in short and angulated necks. It is an effective method of extending the proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Adjunctive techniques such as the push-up or reverse slider techniques have been reported in such cases with more favorable results. 18,19 Indeed, our registry showed no significant differences between the two groups in intraoperative type Ia endoleaks and only a tendency of increased type Ia endoleak postoperatively (3.3% vs 1.5%, p=0.075). Considering the significantly more proximal neck IFU violation observed in the Endurant stent graft, it demonstrates the favorable performance of the Endurant stent graft in the challenging proximal neck cases in our cohort.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Adjunctive techniques such as the push-up or reverse slider techniques have been reported in such cases with more favorable results. 18,19 Indeed, our registry showed no significant differences between the two groups in intraoperative type Ia endoleaks and only a tendency of increased type Ia endoleak postoperatively (3.3% vs 1.5%, p=0.075). Considering the significantly more proximal neck IFU violation observed in the Endurant stent graft, it demonstrates the favorable performance of the Endurant stent graft in the challenging proximal neck cases in our cohort.…”
Section: Discussionmentioning
confidence: 62%
“…Adjunctive techniques such as the push-up or reverse slider techniques have been reported in such cases with more favorable results. 18,19 Indeed, our registry showed no significant differences between the two groups in Log-rank analyses were used to compare between the Endurant and the Excluder groups. There was no significant difference in 5 year overall survival between the Endurant and the Excluder groups (69.7±3.7% vs 75.2±3.2%; p=0.926).…”
Section: Discussionmentioning
confidence: 94%
“…4) Recently, Morikage et al reported the reverse slider technique using the Endurant stent-graft system. 11) This is a method of securing central sealing by pushing up the graft edge while placing it, and it is thought that sealing is possible even with a neck length of 10 mm. Our choice of the Excluder stent-graft system was based on previous experiences and anecdotal evidence from our center where we find it to be the most flexible and adaptable within the blood vessel, resulting in a better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The reverse slider technique was used for adequate proximal sealing. 5 ) A balloon dilatation at the proximal portion of the stent graft was then performed using Gore® Molding & Occlusion Balloon (W. L. Gore and Associates Inc., Flagstaff, AZ, USA) under nominal balloon pressure. Completion angiography revealed that the stent graft was properly placed, with no endoleak and dissection.…”
Section: Case Reportsmentioning
confidence: 99%